O impacto da inteligência artificial na relação dos bancos com os millennials na era pós-digital: um estudo de caso da Bia - Schorn, Bruna (Universidade do Vale do Rio dos Sinos, 2019)
The arrival of the post-digital era is constantly transforming the way people interact with one another, as wells as with objects, and brands. The speed with which this happens causes a behavioral mismatch between the market segments that carry a history of tradition, such as the banking segment, and the new generations, who are highly informed and connected, as the millennials. In those cases, technologies such as Artificial Intelligence, make it possible for brands to have access to data generated with each connection, so they can acquire more knowledge about their audience, adapting their communication strategies, and establishing mutually beneficial relationships. With that in mind, how can banks explore technological resources, such as AI, to synchronize their communication and relationship strategies with millennials' behavioral transformations? Taking these provocations into consideration, the goal of this research is understanding the impact of Artificial Intelligence in Bradesco's relationship with its millennial consumers in the post-digital era. The study was developed through a qualitative descriptive methodology, investigating BIA's (Bradesco Artificial Intelligence) case study through two steps: a) analyzing and interpreting the bank's intention in using the AI in communication and relationship strategies; and b) observing the millennial consumer's perceptions when impacted by these strategies. To support the discussion on the impact of AI use in this relationship a guiding hypothesis was elaborated from the theoretical problematization with Longo (2014) and Gabriel (2019). This initial hypothesis unfolded into five other hypotheses, which, ultimately, were totally validated, partially or not validated during the data analysis and methodological exercise. Lastly, it's understood that the AI is an innovation alternative for Bradesco's means of communication and relationship, and according to the way it's applied, can also estimulate a beneficial mutual relationship.
Keywords: Bancos; Inteligência artificial; Marketing de relacionamento; Millennials; Pós-digital; Artificial Intelligence; Banks; Post-digital; Relationship marketing